Web-Based Exercise Interventions for Children with Neurodevelopmental Disorders - Ikezawa, Natsumi; Yoshihara, Ryo; Kitamura, Masahiro; Osumi, Ayami; Kanejima, Yuji; Ishihara, Kodai; Izawa, Kazuhiro P. (Pediatric reports, 2023)
Various studies have shown the effectiveness of motor interventions for children with neurodevelopmental disorders (NDDs). Web-based interventions may provide an opportunity for remote access to effective interventions with less burden on therapists. This systematic review aimed to examine the effects of web-based exercise interventions for children with NDDs. We searched PubMed for relevant articles published in English since 1994 and included intervention studies focusing on NDDs in children aged ≤18 years, who received web-based exercise interventions. We categorized the extracted information by outcome measure and intervention type and assessed the risk of bias of the included studies. We selected five articles whose subjects had autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), and developmental coordination disorder (DCD). The exercise interventions used active video games, a Zoom-based intervention, and a WhatsApp-based intervention. Three papers showed improvements in physical activity, motor function, and executive function, whereas two papers on DCD showed no improvements in motor coordination or physical activity. Web-based exercise intervention for children with ASD and ADHD may improve their motor function, executive function, and physical activity rather than for children with NDDs. An intervention may be more effective when the content of the intervention is based on objectives and symptoms, when guidance is provided by specialists, or when sufficient explanation and support are provided to parents. However, more research is needed to statistically evaluate the effectiveness of web-based exercise interventions for children with NDDs.